2022
DOI: 10.15294/jpii.v11i1.32983
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Madrasah Teachers' Scientific Competencies Integrated with Scientific Literacy through the STEM Approach

Abstract: This study aims to measure the scientific competence of prospective teachers of Madrasah Ibtidaiyah integrated scientific literacy through a STEM approach. The research method used was descriptive quantitative with a sample of 40 students from the same study program at two different universities. The selected sample has taken basic science courses with a minimum score of B. This research used a purposive sampling technique, where the sampling actively participates in learning activities. Data were collected us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…From the analysis stage, it was found that the material that met the needs of students and teachers was material about a clean and healthy lifestyle for grade V Madrasah Ibtidaiyah (MI) students (Rokhimawan et al, 2022). This material can be presented easily in the form of illustrated stories (comics) that will attract students to learn.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From the analysis stage, it was found that the material that met the needs of students and teachers was material about a clean and healthy lifestyle for grade V Madrasah Ibtidaiyah (MI) students (Rokhimawan et al, 2022). This material can be presented easily in the form of illustrated stories (comics) that will attract students to learn.…”
Section: Resultsmentioning
confidence: 99%
“…One of them can help humans in learning science and present innovations for technology media-based learning, the development of information and communication technology as a tool that can develop according to the demands of the times to offer new things for education (Bali et al, 2019). In applying technology to education, two basic conditions are required: the technology must make teaching strategies more effective and the technology must always be available and accessible (Robson, 2003). One of the latest learning media that is very accessible is mobile learning (Firdawati et al, 2021;Yulianci et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In the Indonesian databases, 17 articles were published in seven of 54 Sinta STEM-related journals. Six articles (Irwanto et al, 2022;Ngabekti et al, 2019;Rokhimawan et al, 2022;Rosana et al, 2021;Rusydiyah et al, 2021;Yulianti et al, 2022) All of the 110 researchers published at most 1 article as first author. The authors in our corpus published at most two articles, either one as the first author or both as coauthors.…”
Section: Research Trajectorymentioning
confidence: 99%
“…The authors in our corpus published at most two articles, either one as the first author or both as coauthors. Winarno (in Mayasari et al, 2019 andWinarno et al, 2017) and Susilawati (in Rokhimawan et al, 2022 andRusydiyah et al, 2021) are two other researchers who published two articles. Nevertheless, although it could be assumed that there are currently no particular researchers dominating the Indonesian field, the number of researchers involved and the collaboration that has been established have become the embryo for the development of STEM implementation and research for PSTs in Indonesia.…”
Section: Research Trajectorymentioning
confidence: 99%
See 1 more Smart Citation